The effect of blending methods on the properties of PLA/Gr nanocomposites. - Norazlina, Hashim; N. R. B., Amin; S., Abdullah; Abdul Hadi, Abdullah; N., Abdullah; R. M., Mohamed; N. A., M. Yahya; Kamal, Yusoh (IOP Publishing, 2020)
Polymer nanocomposites based on polylactic acid (PLA) and graphene (Gr) were blended via melt blending and solution mixing. The properties of hardness and melt flow index (MFI) were investigated with variables of Gr loading from 0.5–2.0 wt.% and the effect of poly(ethylene glycol) (PEG) as plasticizer. The PLA/Gr nanocomposites exhibited higher hardness compared with neat PLA for both methods of nanocomposites preparation which were due to stiffness effect from nanofiller. The loading of PEG in the PLA nanocomposites resulted in the slightly decreasing of hardness. The hardness of PLA and PLA nanocomposites obtained from melt blending were higher than hardness from solution mixing where 2.0 wt.% Gr loading in PLA exhibited maximum value which was 83.1 Shore D. The significant improvement on the MFI could be seen with plasticizer loading compared to unfillled PEG in PLA blends obtained from both methods. Again, the MFI values of PLA/Gr showed from melt blending were higher than exhibited from solution blending method. The highest MFI was 70.6 g/10 min, obtained from 0.5 wt.% Gr loading in PLA/PEG/Gr nanocomposite. The morphology study from Field Emission Scanning Electron Microscopy (FESEM) analysis confirmed the interfacial interaction and homogeneity of Gr in PLA in order to enhance the hardness and MFI properties as discussed above